Fatal case of sorafenib-associated idiosyncratic hepatotoxicity in the adjuvant treatment of a patient with renal cell carcinoma. - Fairfax, B; Pratap, S; Roberts, I; Collier, J; Kaplan, R; Meade, A; Ritchie, A; Eisen, T; Macaulay, V; Protheroe, A (BioMed Central, 2012)
BACKGROUND: Sorafenib is an orally available kinase inhibitor with activity at Raf, PDGFβ and VEGF receptors that is licensed for the treatment of advanced renal cell carcinoma (RCC) and hepatocellular carcinoma (HCC). Current evidence-based post-nephrectomy management of individuals with localized RCC consists of surveillance-based follow up. The SORCE trial is designed to investigate whether treatment with adjuvant sorafenib can reduce recurrence rates in this cohort. CASE PRESENTATION: Here we report an idiosyncratic reaction to sorafenib resulting in fatal hepatotoxicity and associated renal failure in a 62 year-old man treated with sorafenib within the SORCE trial. CONCLUSION: This is the first reported case of sorafenib exposure associated fatal toxicity in the adjuvant setting and highlights the unpredictable adverse effects of novel adjuvant therapies.